Gender knowledge for mitigating climatic risks - Agarwal, Tripti (International Maize and Wheat Improvement Center, 2018)
Presented by Tripti Agarwal (CIMMYT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.